2013
DOI: 10.1002/adsc.201300664
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Carbonyl‐Based Catalyst for Hydrosilylation of Carboxamides

Abstract: International audienceThe cobalt carbonyl [Co2(CO)8] complex is employed as a useful catalyst for the reduction of tertiary amides to the corresponding tertiary amines using 1,1,3,3-tetramethyldisiloxane (TMDS) and poly(methylhydrosiloxane) (PMHS) as silane reagents under thermal (100 °C) or photo-assisted conditions (UV, 350 nm at room temperature). Of particular interest, a low catalytic amount (0.5 mol%) of [Co2(CO)8] is used to perform the reaction with 2.2 equiv. of PMHS at 100 °C for 3 h. This reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…Cobalt is one of the earthabundant metals; thus cobalt catalysts are all the more appreciated as they provide precious hydrogenation performances, 470 even in the TH process. 471,472 An easily accessible cobalt complex 117 showed excellent activity in diverse ranges of substrates including ketones, aldehydes, imines, and α,β-unsaturated carbonyls, and provided the alcohol and amine products in 94−99% yields with TH under mild conditions (Scheme 43). 473 Interestingly, the use of conjugated substrates including trans-4-phenyl-3-buten-2-one and cinnamaldehyde revealed that both CC and CO were completely reduced, affording the corresponding alcohols in 98% and 95% yields, respectively.…”
Section: Osmium-based Catalystsmentioning
confidence: 99%
“…Cobalt is one of the earthabundant metals; thus cobalt catalysts are all the more appreciated as they provide precious hydrogenation performances, 470 even in the TH process. 471,472 An easily accessible cobalt complex 117 showed excellent activity in diverse ranges of substrates including ketones, aldehydes, imines, and α,β-unsaturated carbonyls, and provided the alcohol and amine products in 94−99% yields with TH under mild conditions (Scheme 43). 473 Interestingly, the use of conjugated substrates including trans-4-phenyl-3-buten-2-one and cinnamaldehyde revealed that both CC and CO were completely reduced, affording the corresponding alcohols in 98% and 95% yields, respectively.…”
Section: Osmium-based Catalystsmentioning
confidence: 99%
“…Described herein is a[ Mo-(CO) 6 ]-catalyzed protocol with an unprecedented chemoselectivity and allows for the reduction of amides in the presence of aldehydes and imines.F urthermore,t he system proved to be tunable by variation of the temperature,w hiche nabled for either C À Oo rC À Nb ond cleavage that ultimately led to the isolation of both amines and aldehydes,r espectively,i nh igh chemical yields. Described herein is a[ Mo-(CO) 6 ]-catalyzed protocol with an unprecedented chemoselectivity and allows for the reduction of amides in the presence of aldehydes and imines.F urthermore,t he system proved to be tunable by variation of the temperature,w hiche nabled for either C À Oo rC À Nb ond cleavage that ultimately led to the isolation of both amines and aldehydes,r espectively,i nh igh chemical yields.…”
mentioning
confidence: 99%
“…[1] Several research groups have focused on the development of protocols for hydrosilylation of amides, which have led to an umber of catalytic systems based on the platinum-group metals, [2] as well as Fe, [3] Zn, [4] Au, [5] Co, [6] In, [7] Mg, [8] and B. [1] Several research groups have focused on the development of protocols for hydrosilylation of amides, which have led to an umber of catalytic systems based on the platinum-group metals, [2] as well as Fe, [3] Zn, [4] Au, [5] Co, [6] In, [7] Mg, [8] and B.…”
mentioning
confidence: 99%
“…78 Various N,N-dibenzylbenzamide derivatives, N,Ndialkylamides, aliphatic amides and benzamides derived from pyrrodine, piperidine and morpholine were successfully reduced to the corresponding amines using 0.5 mol% of Co 2 (CO) 8 C35, 2.2 equiv. of PMHS in toluene at 100 o C after 3-16 h. (Scheme 36) This reaction could also be performed under UV irradiation, but with TMDS as reducing reagent.…”
Section: Cobalt Catalystsmentioning
confidence: 99%